Baptism, brotherhood, and belief in Reformation Germany Anabaptism and Lutheranism, 1525-1585 - Hill, Kat (Oxford historical monographs., 2015)
This title deals with the historically neglected Anabaptist movement in Reformation Germany, exploring how ordinary Anabaptists interpreted and interacted with Lutheran theology and how their beliefs shaped religious identity in the Reformation era.